2022
DOI: 10.1002/eat.23839
|View full text |Cite
|
Sign up to set email alerts
|

Gastric dilatation in patients with restrictive eating disorders

Abstract: Objectives To better understand gastric dimensions in patients diagnosed with restrictive eating disorders (EDs). Method In this retrospective study, 56 patients, with restrictive EDs, and 60 gender/age/race‐matched patients from an outpatient clinic, were studied. Difference in stomach size, between cohorts, was ascertained, and regression analyses were used to examine associations with stomach size in the ED cohort. Results Patients with EDs were found to have significantly enlarged gastric dimensions when c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…These data are in line with those recently reported from data obtained in a lying position by Gibson et al. (2022), among female patients suffering from restrictive eating disorders. Our findings corroborate the results of Gibson's study, highlighting the presence of gastric dilatation in AN, independently of the presence of radiological signs of SMAS, which were found in about a third of our patients.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These data are in line with those recently reported from data obtained in a lying position by Gibson et al. (2022), among female patients suffering from restrictive eating disorders. Our findings corroborate the results of Gibson's study, highlighting the presence of gastric dilatation in AN, independently of the presence of radiological signs of SMAS, which were found in about a third of our patients.…”
Section: Discussionsupporting
confidence: 93%
“…The main objective of this study was to describe stomach morphometry on UGR in patients with AN, further to the study by Gibson et al. reporting gastric dilatation in patients with restrictive eating disorders using CT images (Gibson et al., 2022). To this end, we developed a novel SSI, calculated as the ratio of stomach height to abdominal height (described in Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A paper recently published by Gibson et al (2022) [8] sought to define baseline gastric dimensions in patients with eating disorders. This study found that the average stomach size in patients with eating disorders was significantly larger than a control cohort, leading the authors to conclude that malnutrition, resulting from restrictive eating disorders may be associated with an enlarged stomach.…”
Section: Discussionmentioning
confidence: 99%